The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2147/jbm.s36249
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of eculizumab for atypical hemolytic uremic syndrome

Abstract: The biology of atypical hemolytic uremic syndrome has been shown to involve inability to limit activation of the alternative complement pathway, with subsequent damage to systemic endothelial beds and the vasculature, resulting in the prototypic findings of a thrombotic microangiopathy. Central to this process is the formation of the terminal membrane attack complex C5b-9. Recently, application of a monoclonal antibody that specifically binds to C5, eculizumab, became available to treat patients with atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 117 publications
0
19
0
1
Order By: Relevance
“…Thrombotic microangiopathy (TMA) is a clinical syndrome that manifests with microangiopathic hemolytic anemia, thrombocytopenia, and end-organ damage secondary to arteriolar and capillary microthrombi and endothelial injury. 1 Atypical hemolytic uremic syndrome (aHUS) is a rare form of TMA caused by overactivity of the alternative pathway of complement, with high rates of morbidity and mortality. 1 Genetic anomalies in the alternative pathway of complement are seen in 60% of cases of aHUS and are responsible for excessive complement activation.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombotic microangiopathy (TMA) is a clinical syndrome that manifests with microangiopathic hemolytic anemia, thrombocytopenia, and end-organ damage secondary to arteriolar and capillary microthrombi and endothelial injury. 1 Atypical hemolytic uremic syndrome (aHUS) is a rare form of TMA caused by overactivity of the alternative pathway of complement, with high rates of morbidity and mortality. 1 Genetic anomalies in the alternative pathway of complement are seen in 60% of cases of aHUS and are responsible for excessive complement activation.…”
Section: Introductionmentioning
confidence: 99%
“…Improving HRQoL should be considered while utilizing costly medications as a treatment option for prolonging life for a short length of time [ 47 ]. Eculizumab, a monoclonal antibody that specifically binds to C5 has been widely used worldwide for the treatment of aHUS [ 48 ]. The present study demonstrates that treatment with the eculizumab significantly improves HRQoL in patients with aHUS [ 27–29 , 41–46 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only two reviews have reported the data of HRQoL in aHUS population [ 48 , 50 ]. However, none of the studies reported the performance of patient self-reported HRQoL instruments applicable for aHUS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Eculizumab, a terminal complement inhibitor, is approved for the treatment of aHUS to control the thrombotic microangiopathy (TMA) manifestations and to avoid the relapses of the disease. In the post-kidney transplantation, many studies have already described the same effect [ 20 , 21 ]. However, long-term studies combining eculizumab to immunosuppressive agents used in post-kidney transplantation are lacking[ 22 ].…”
Section: Introductionmentioning
confidence: 92%